Urgensi Pendidikan Agama Islam Dalam Membentuk Karakter Anak Di Sekolah Dasar - Miftakhuddin Miftakhuddin; Imron Imron (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The phenomenon that shows that there is a lot of moral decline can result in thevulnerability of religious moral values to students. This can cause several negativeimpacts, including brawls between students, anarchic demonstrations, drug use,promiscuity, deviant behavior, and many other negative impacts. For this reason, a goodmoral or character formation is needed for children through Islamic religious learning inschools. Moral or moral is one of the main teachings of Islam that must be prioritized inIslamic education to be taught or instilled in students, with the intention of formingpeople with strong and good personalities (morals).This paper is a reminder for us that religious education has an important role incharacter building in elementary schools. We also gain knowledge about the method ofimplementing the learning process of Islamic religious education in the formation of thecharacter of Abdurrahman an-Nahlawi's perspective.